Optimisation Approach and Influence of Composition and Curing Parameters on Algerian Geopolymer Paste Compressive Strength Based on Metakaolin and Slag Local Materials - Zeghichi Leila; Mehsas boumedienne; Benghazi zied (Current Overview on Science and Technology Research Vol. 10, 2022)
The alkali-activated cement has been proposed as an alternative to Portland cement and has shown good physical, mechanical, and durability properties as well as low environmental impacts. This work aims to study the production of Metakaolin/Blast furnace slag (MK/S) based geopolymer. We investigated the influence of metakaolin content, the concentration in the alkaline solution, the SiO2/Na2O molar ratio, the curing temperature, and the curing time using a full factorial design with two levels to observe how the variation of these parameters promotes the modifications on the fresh and hardened properties of produced geopolymer. Then, we analysed the optimisation of the main parameter effect, the interactions, and the predicted response of the generated model using factorial design in statistical software JMP Trial 16. The parameters such as molar ratio MR (1.5 - 2), the density of solutionDS (1.3 -1.4) g/cm3, the curing temperature of oven OT(60- 100)C° and the curing time CT (6- 48)h were considered for each combination of MK/S: [(50 % MK / 50%S), ( 80 % MK /20%S ) and ( 100 % MK/ 0 % S)].